Differential predictors of early- and delayed-onset post-traumatic stress disorder following physical injury: a two-year longitudinal study - Kang, Sung-Gil; Kim, Ju-Wan; Kang, Hee-Ju; Jang, Hyunseok; Kim, Jung-Chul; Lee, Ju-Yeon; Kim, Sung-Wan; Shin, Il-Seon; Kim, Jae-Min (Frontiers in Psychiatry, 2024)
Objectives This study aimed to investigate the predictors of both early- and delayed-onset PTSD over a 2-year period following physical injuries. Methods Patients were recruited from a trauma center at a university hospital in South Korea (June 2015 ~ January 2021). At baseline, 1142 patients underwent comprehensive assessments including socio-demographic, pre-trauma, trauma-related, and peri-trauma evaluations. Diagnoses of acute stress disorder (ASD) and subthreshold ASD were also determined using the Clinician-administered PTSD Scale (CAPS). Follow-up assessments at three months included diagnoses of PTSD and subthreshold PTSD using CAPS, and stressful life events (SLEs), with additional evaluations at 6, 12, and 24 months. The analyzed sample comprised 1014 patients followed up at least once after the baseline and 3-month evaluations. PTSD diagnoses were categorized into early-onset (within the first six months after trauma) and delayed-onset (more than six months after trauma). Logistic regression models identified predictors for each group. Results Early-onset and delayed-onset PTSD were diagnosed in 79 and 35 patients, respectively. Early-onset PTSD was predicted by previous psychiatric disorders, previous traumatic events, ASD and subthreshold ASD diagnoses, and higher anxiety levels. In contrast, delayed-onset PTSD was linked to higher education, higher injury severity, and subthreshold PTSD and SLEs at 3-month follow-up. Conclusion Distinct predictors were found for early-onset and delayed-onset PTSD. The findings underscore the heterogeneous factors influencing the temporal development of PTSD post-trauma, and may provide valuable guidance for more targeted interventions and improved patient outcomes.